2018
DOI: 10.1002/jper.18-0417
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years later: Oral health‐related quality of life and standard of treatment in patients with chronic periodontitis

Abstract: Background To assess oral health‐related quality of life (OHRQoL) after long‐term (20 years) periodontal treatment in patients with chronic periodontitis (ChP) and to compare it with the current clinical outcome and oral health status. Methods Twenty years after therapy, 63 patients were reexamined. The dental and periodontal status and OHRQoL using the Oral Health Impact Profile‐G49 (OHIP‐G49) were assessed. Descriptive statistics, correlation analysis, and tests for differences were calculated. Results Up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 36 publications
4
28
1
1
Order By: Relevance
“…Moreover, our cohort is older (71 years) than the general German population (44 years; BIB, 2019), which may impact on OHIP-G14, as discussed below. Impairment in our population largely occurred in the subdomains "psychological disability" and "physical pain," affirming the outcomes of previous studies which found that periodontitis can cause pain (El Sayed et al, 2018) and impacts on patients' psychological perception (Bäumer et al, 2018;Sonnenschein et al, 2018).…”
Section: T0 T1 a T2supporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, our cohort is older (71 years) than the general German population (44 years; BIB, 2019), which may impact on OHIP-G14, as discussed below. Impairment in our population largely occurred in the subdomains "psychological disability" and "physical pain," affirming the outcomes of previous studies which found that periodontitis can cause pain (El Sayed et al, 2018) and impacts on patients' psychological perception (Bäumer et al, 2018;Sonnenschein et al, 2018).…”
Section: T0 T1 a T2supporting
confidence: 87%
“…Compliance and smoking status have been found to be positively associated with patients’ oral health perception according to El Sayed et al. (2018). Similarly, age was found to be associated with OHRQoL, with older individuals showing a better OHRQoL (indicating some kind of coping mechanism found in the elderly).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also has a negative impact on OHRQoL, nutrition, speech, social interactions and psychological well-being and is associated with several systemic diseases (Linden & Herzberg, 2013;Reynolds & Duane, 2018). Currently, generic OHRQoL measures like the Oral Health impact Profile (OHIP) is used worldwide for assessing OHRQoL in patients with chronic periodontitis (El Sayed et al, 2019;He, Wei, Wang, & Ji, 2018). However, generic measures of health status may not be sensitivity enough to capture clinical changes than disease-specific tools (Locker & Allen, 2007).…”
mentioning
confidence: 99%
“…Females may have worse OHRQoL (Brauchle et al, 2013; Fotedar et al, 2014), or men may report lower impacts (Wellapuli & Ekanayake, 2016). However, other studies report no gender difference in participants with periodontitis (El Sayed et al, 2019; Miao et al, 2016; Saito et al, 2010).…”
Section: Discussionmentioning
confidence: 91%